Effects of soil amendment treatments on growth, yield and fruit quality of selected banana (Musa AAA) cultivars - Elkashif, Mohamed E; Elamin, Osman M; Mahmoud, Haroun I; Abbass, Mohamed A. (Gezira Journal of Agricultural Science, 2014)
Banana cultivation in Sudan is restricted to the narrow strip of silt deposits along the banks of the Blue Nile and the River Nile. Hence, there is a need to expand banana cultivation in the high terrace, heavy clay soils. Banana performance in heavy clay soils is very poor, unless soil amendments are applied. Therefore, the objective of this research was to study the effects of soil amendment treatments on growth, yield and fruit quality of selected banana cultivars. The experiment was conducted in the Research Farm of the National Institute for the Promotion of Horticultural Exports, University of Gezira, during 2009-2011. Treatments consisted of three selected banana cultivars : Two introduced cultivars, namely, Grand Nain 1824 (GN) and William’s Hybrid 172 (WH) and the local cultivar Dwarf Cavendish (DC). Soil amendment treatments were : 1, 50% heavy clay (HC) + 50% loam (L); 2, 50% HC + 50% chicken manure (CM); 3, 50% HC + 25% L + 25% CM; 4, 33% HC + 33% L + 34% CM; 5, 100% HC (control). Treatments were arranged in a randomized complete block design with three replicates. Results showed that the introduced cultivars GN and WH had more vigorous vegetative growth, higher yield components, total yield and better fruit quality than the local cultivar DC. Soil amendment treatments of 50% HC + 25% L + 25% CM and 33% HC + 33% L + 34% CM resulted in the most vigorous vegetative growth, the highest yield components and total yield and the best fruit quality, followed by 50% HC + 50% L and 50% HC +50%CM, whereas the least vegetative growth, the lowest yield components, total yield and the worst fruit quality were produced by bananas grown in 100% HC (control). In order to expand banana production for the local market and export, it is recommended to amend heavy clay soils with loams and chicken manure at 33% each and grow the introduced cultivars GN and WH.      تنحصر زراعة الموز في السودان على الشريط الضيق للتربة الغرينية على ضفاف النيل الأزرق ونهر النيل. هنالك حاجة ماسة للتوسع في زراعة الموز في السودان ولذلك لا بد من محاولة زراعته في الاراضي الطينية الثقيلة و التي لا تصلح لزراعة الموز إلا إذا تمت بعض المعالجات. لذلك فإن الهدف من هذا البحث هو دراسة تأثير بعض مستصلحات التربة على النمو ومكونات الإنتاج والإنتاج الكلي لثلاثة أصناف منتخبة من الموز في هذا النوع من الأراضي. أجريت التجربة في مزرعة بحوث المعهد القومي لتنمية الصادرات البستانية بجامعة الجزيرة خلال الفترة 2009-2011. اشتملت المعاملات على ثلاثة أصناف منتخبة من الموز: صنفان مستجلبان من خارج السودان وهما جراندنين 1824 (GN) وهجين وليامز172 (WH) بالإضافة إلى الصنف المحلي الكافندش القزم (DC). إشتملت مستصلحات التربة على: (1) 50% تربة طينية ثقيلة + 50% تربة غرينية ، (2) 50% تربة طينية + 50% ماروق دواجن ، (3) 50% تربة طينية + 25% تربة غرينية + 25% ماروق دواجن، (4) 33% تربة طينية + 33% تربة غرينية + 34% ماروق دواجن ، (5) 100% تربة طينية (شاهد). أستخدم تصميم القطع العشوائية الكاملة  بثلاثة مكررات . أظهرت النتائج أن الأصناف المستجلبة من الخارج GN وWH كانت أفضل في النمو الخضري وأعلى إنتاجية وأفضل جودة للثمار من الصنف المحلي DC. معاملات مستصلحات التربة 50% تربة طينية + 25% تربة غرينية + 25% ماروق دواجن و 33% تربة طينية و33% تربة غرينية و34% ماروق دواجن أعطت أفضل نمو خضري وأعلى إنتاجية وأفضل نوعية للثمار ، تليها المعاملات 50% تربة طينية + 50% تربة غرينية و50% تربة طينية + 50% ماروق دواجن. أما زراعة الموز في الأراضي الطينية الثقيلة بدون مستصلحات أدت  إلى أقل نمو خضري وأقل إنتاجية وأدنى نوعية للثمار. لذلك لكي يتم التوسع في زراعة الموز فى الاراضى الطينية الثقيلة للسوق المحلي والتصدير ، فإنه يوصى بإضافة  التربة الغرينية و ماروق الدواجن بنسبة 33% لكل منهما وزراعة الأصناف المستجلبة GN و WH.